2021
DOI: 10.1039/d1sc04582b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of (dppf)nickel-catalysed Suzuki–Miyaura cross-coupling reactions by α-halo-N-heterocycles

Abstract: A nickel/dppf catalyst system was found to successfully achieve the Suzuki-Miyaura cross-coupling reactions of 3- and 4-chloropyridine but not 2-chloropyridine and other α-halo-N-heterocycles. Further investigations revealed that chloropyridines undergo rapid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In 2021, Nelson et al reported the SM coupling of 3-and 4chloropyridines using Ni(cod)(dppf). 58 They found that 2chloropyridine underwent dimerization (Scheme 19). A similar dimerization proceeded in the reaction of -halo-N-heterocycles (2-chloropyridine, 2-chloroquinoline).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…In 2021, Nelson et al reported the SM coupling of 3-and 4chloropyridines using Ni(cod)(dppf). 58 They found that 2chloropyridine underwent dimerization (Scheme 19). A similar dimerization proceeded in the reaction of -halo-N-heterocycles (2-chloropyridine, 2-chloroquinoline).…”
Section: Template For Synthesis Thiemementioning
confidence: 99%
“…The modern synthesis of aromatic frameworks often employs palladium-catalyzed Suzuki–Miyaura coupling (Pd-SMC) between aryl electrophiles, such as halides, and arylboron nucleophiles to construct Csp 2 –Csp 2 bonds (Scheme A). , The growing focus on sustainable pharmaceutical production with a minimal environmental impact, along with the motivation to reduce process costs, has led to an increase of interest in pursuing nonprecious metal alternatives to the Pd-SMC process . Nickel, belonging to the same group as palladium, emerges as a potential substitute. However, implementing Ni-SMC in process synthesis poses challenges, including the requirement for high catalyst loading (typically ranging from 5 to 10 mol %), which offsets the cost benefit, a slow reaction rate, and a limited scope of heteroarenes (Scheme B). , The latter limitation may arise from potential catalyst poisoning through coordination.…”
Section: Introductionmentioning
confidence: 99%
“…4−10 However, implementing Ni-SMC in process synthesis poses challenges, including the requirement for high catalyst loading (typically ranging from 5 to 10 mol %), 11 which offsets the cost benefit, a slow reaction rate, 12 and a limited scope of heteroarenes (Scheme 1B). 13,14 The latter limitation may arise from potential catalyst poisoning through coordination.…”
Section: ■ Introductionmentioning
confidence: 99%